Dexmedetomidine to enable MRI scanning in a patient with airway compromise. Issue 2 (28th October 2014) - Scott‐Warren, Victoria; Sebastian, Joseph; Eadsforth, Peter
Summary: We present the case of an obese gentleman with airway compromise due to a large tumour within the left thoracic inlet, who required a magnetic resonance imaging (MRI) scan to plan further treatment. He was profoundly claustrophobic and required sedation in order to undergo the scan. We describe the use of dexmedetomidine supplemented with a small amount of midazolam to successfully sedate the patient whilst avoiding respiratory depression and obtundation of airway reflexes associated with higher doses of midazolam or propofol sedation.